Case Report: Hydroa vacciniforme-like lymphoproliferative disorder, an EBV-associated disease, successfully treated with hematopoietic stem cell transplantation - Liquidano-Perez, Eduardo; Maza-Ramos, Gibert; Yamazaki-Nakashimada, Marco; Rodríguez-Jurado, Rodolfo; Ramírez Ristori, Alfonso G.; Bustamante-Ogando, Juan Carlos; Cruz-Munoz, Mario Ernesto; Gutierrez-Guerrero, Arturo; Saez-de-Ocariz, Marimar; Espinosa-Padilla, Sara; Ramirez-Uribe, Nideshda; Scheffler-Mendoza, Selma C. (Frontiers in Immunology, 2025)
IntroductionThe hydroa-vacciniforme-like lymphoproliferative disorder (HVLD) is a rare NK/T-cell condition affecting children in Latin America and Asia. It often progresses to systemic lymphoma, with Latin American patients experiencing worse outcomes compared to East Asians. Understanding viral and host genetic interactions is crucial for advancing targeted therapies. Here, we report a male patient with HVLD successfully treated with hematopoietic stem cell transplantation, highlighting its potential as a therapeutic approach for this aggressive disease.Case descriptionAn 8-year-old boy presented with persistent skin lesions, fever, and pain. Biopsy confirmed a diagnosis of HVLD. Initial treatments with thalidomide and steroids provided temporary relief. At 12, lymphoma progression led to rituximab and CHOP chemotherapy. Further investigations revealed persistent EBV infection and lymphoma; hence, a haploidentical stem cell transplant was performed at 15. The procedure was successful, achieving complete immune reconstitution and viral clearance. Three years post-transplant, the patient remains in good health with no detectable EBV and complete vaccinations.DiscussionWhile EBV infection is common, only specific immunodeficiency states seem to enable EBV-related lymphoproliferative disorders. The exact mechanism leading to this immunosuppressive environment in HVLD remains unclear. Clinically, HVLD resembles specific inborn errors of immunity with EBV susceptibility. Additionally, cases of GATA2 and TACI deficiency presenting with HVLD suggest a potential link to underlying immune dysfunction. Further research in this area is crucial to understand the immunological basis of HVLD. Treatment options for HVLD are diverse and lack standardized protocols. Our case demonstrates the potential of HSCT with reduced-intensity conditioning and EBV-specific T-cell infusion as an effective cure. Given the limited understanding of HVLD, an immunological approach to characterizing patient profiles and prolonged follow-up are essential. While diverse therapies exist, HSCT offers the best hope for a cure. Further research towards tailored treatment strategies holds significant promise for improved patient outcomes.ConclusionHVLD presents a complex and multifaceted challenge; our case demonstrates the potential of HSCT as a curative treatment. Unveiling the underlying immunology and tailoring therapies to patient profiles are crucial for improved outcomes. Further research is key to refining treatment strategies and offering hope for this rare and severe disease.